2016
DOI: 10.1007/s10551-016-3367-4
|View full text |Cite
|
Sign up to set email alerts
|

Do Entrepreneurial SMEs Perform Better Because They are More Responsible?

Abstract: Many scholars have investigated the direct impact of entrepreneurial orientation (EO) on performance, but this direct association seems both spurious and ambiguous because many parameters may have an indirect influence on this relationship. The present study thus considers sustainable practices-environmental practices, social practices in the workplace (SPW), and social practices in the community (SPC)-as three probable mediators in the relationship between EO and performance, which is considered in terms of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 147 publications
(250 reference statements)
1
59
1
1
Order By: Relevance
“…Because the implementation of corporate sustainability in small businesses often occurs informally and is not necessarily reflected in explicit management systems (Perrini et al, ; Russo & Tencati, ), indicators were selected to be applicable to all respondents regardless of whether they deliberately pursued CS issues. Moreover, in accordance with the European Commission () and previous academic papers (e.g., Baumann‐Pauly et al, ; Courrent, Chassé, & Omri, ), social practices were distinguished based on the external (community practices) and internal (workplace practices) stakeholders concerned.…”
Section: Methodsmentioning
confidence: 85%
See 1 more Smart Citation
“…Because the implementation of corporate sustainability in small businesses often occurs informally and is not necessarily reflected in explicit management systems (Perrini et al, ; Russo & Tencati, ), indicators were selected to be applicable to all respondents regardless of whether they deliberately pursued CS issues. Moreover, in accordance with the European Commission () and previous academic papers (e.g., Baumann‐Pauly et al, ; Courrent, Chassé, & Omri, ), social practices were distinguished based on the external (community practices) and internal (workplace practices) stakeholders concerned.…”
Section: Methodsmentioning
confidence: 85%
“…As some researchers have noted, the spread of sustainability messages in society has contributed to more sustainable practices (Campbell, ; Carroll & Shabana, ; Glavas & Kelley, ; Holt & Barkemeyer, ; Revell et al, ) in both personal and professional life. However, the public debate on sustainability mainly focuses on the environmental aspects and often ignores social issues (Courrent et al, ). Our findings reveal a need for a more balanced treatment of all sustainability dimensions in sensitization campaigns.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, data are confined to companies located in two different but particular national contexts (Spain and Mexico). Although our results have been partially confirmed in other countries such as France (Courrent et al ., ), the extent to which they can be generalised to other geographical contexts and institutional settings remains questionable.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies confirmed that SMEs are powerful source of improving standards of living, employment rate, and innovations (Ayuso & Navarrete-Báez, 2018;Courrent, Chassé, & Omri, 2016;Metaxiotis, 2009;Mutuala & Brakel, 2006;Ongori & Migrio, 2010;Scupola, 2009). SMEs had to gain optimal benefits from human capital and technologies in order to get strength in knowledge economy.…”
mentioning
confidence: 99%